Exploring knowledge of prospective biology teacher about Education for Sustainable Development - Ivo Novidsa; Widi Purwianingsih; R. Riandi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Education for Sustainable Development (ESD) is crucial program hold by United Nations in realizing the Sustainable Development Goals (SDGs). It is necessary to prepare competent teacher which can be started with debriefing through lectures. The purpose of this study was to analyze the prospective biology teacher's knowledge about ESD. The ESD competencies which were analyzed in this study including knowledge, actions, ethical values, attitudes, and emotions. The research subjects used were 30 students of their third year biology teacher education and taking Kapita Selekta Biology course in Universitas Pendidikan Indonesia (UPI). This descriptive study used a questionnaire about knowledge on ESD given to prospective biology teachers before they were given a briefing about ESD. The data gained were analyzed using percentage. The results showed that the persentage of knowledge of prospective biology teachers about ESD was still low (under 50%). Based on the findings, it is necessary to do ESD debriefing so that prospective biology teachers are able to integrate ESD in their learning design